Isotretinoin treatment and risk of depression in acne vulgar patient: what is the evidence? - Diana Santos; Ana Sousa; Maria Matos; Francisco Fertusinhos; Rosa Pendás (Sociedade Portuguesa de Dermatologia e Venereologia, 2022)
Introduction: Acne vulgaris is a chronic inflammatory skin disease that often affects teenagers and young adults. The approach and treatment depend on the location, morphology, and severity of acne. Oral isotretinoin, used in the treatment of severe or refractory nodular acne, may be related to the development of psychiatric pathologies, such as depression or suicidal ideation. The aim of this review is to determine whether isotretinoin treatment is associated with the development of depression in patients with acne vulgaris. Methods: A systematic review of scientific evidence published in electronic databases, using the MeSH terms isotretinoin, acne, and depression. The Strength of Recommendation Taxonomy Scale was used to assess the studies' quality and the recommendation's strength. Results: A total of 142 articles were identified and five met the inclusion criteria: two meta-analyses and three cohort studies (two prospective and one retrospective study). Discussion: The risk of depression associated with taking isotretinoin by acne patients has been a concern and a controversial topic, however, the results are consensual in stating that there doesn't seem to exist any evidence of this association. It was also found that acne treatment, regardless of drug, seems to improve depressive symptoms. The heterogeneity of the studies, the small sample size, and the absence of randomized clinical trials are some limitations. More studies are needed to confirm these findings.